The use of Baamboozle interactive media to increase students' learning activity in ipas learning in grade VI SDIT Mumtaz Al-Bantani - Choirunnisa, Beby Meira; Supriatna, Encep (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This study aims to describe the use of Baamboozle interactive media in increasing students' learning activity in Natural and Social Sciences (IPAS) learning in grade VI Al-Zahrawi SDIT Mumtaz Al-Bantani. In fact, learning that still uses the lecture method causes students to often be less active during the learning process which also has an impact on the low understanding of the material being taught. Therefore, the researcher used Baamboozle interactive media based on educational games as a positive impact to increase student learning activity. This study uses a qualitative approach with a qualitative descriptive method, where data is collected through field observations, interviews with teachers and students, and documentation. The data collected was analyzed qualitatively to describe the phenomenon that occurred, taking into account various supporting and inhibiting factors for the use of Baamboozle interactive media. The results show that the use of Baamboozle can create a more interesting and enjoyable learning atmosphere so that it has an impact on increasing students' active participation. Activities such as discussions, cooperation in study groups, and enthusiasm in participating in the games that took place showed that this media was able to increase students' activeness in learning science materials from the Six Continents in the World. Based on these findings, this research is expected to be able to be a means for teachers to utilize Baamboozle interactive media as an alternative to increase student activity and involvement in learning, especially IPAS learning.
Keywords: Baamboozle; learning activity; learning